The Effect of Contextual-Based Concrete Visual Media Using the Stamp Game on Improving Addition Skills in Slow Learner Students at Junior High School - Rusdin, Arniwati; Mumpuniarti, Mumpuniarti (Journal of Innovation and Research in Primary Education, 2025)
Mathematics education faces significant challenges among slow learner students, with only 30% mastering basic addition operations in special schools. This study investigated the effectiveness of contextual-based concrete visual stamp game media on improving integer addition skills among slow learner students in junior high school. A single-subject research design with A-B-A model was employed involving two seventh-grade male slow learner students (IQ 70-90) from SMP Negeri 1 Teluk Pandan. The study consisted of three phases: baseline A1 (3 sessions), intervention B (4 sessions using stamp game media), and baseline A2 (3 sessions). Data were collected through objective tests and analyzed using visual graph analysis techniques, including within-condition and between-condition analyses. Both subjects demonstrated substantial improvements during the intervention phase. Subject ADR's performance increased from a baseline mean of 52% to 81% during intervention, while Subject MIP improved from 46.67% to 81%. The percentage of non-overlapping data showed 0% overlap between baseline A1 and intervention phases, indicating strong treatment effectiveness. Maintenance phase results revealed differential retention patterns, with Subject ADR maintaining scores above baseline levels (75.67%) and Subject MIP showing continued improvement (87.67%). Contextual-based concrete visual stamp game media significantly enhances integer addition skills among slow learner students. The intervention's effectiveness is attributed to its concrete nature, which facilitates the transition from concrete to abstract thinking consistent with constructivist learning principles. These findings support the integration of manipulative tools in inclusive mathematics education for students with diverse learning needs.